The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1139/f92-177
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Level Relationships in Pelagic Food Webs: Comparisons Derived from Long-Term Data Sets for Oneida Lake, New York (USA), and Lake St. George, Ontario (Canada)

Abstract: We used standardized methods to analyze a 14-yr data set from Oneida Lake and a 10-yr data set from Lake St. George. We estimated mean summer concentrations of several trophic level indicators including piscivores, planktivores, zooplankton, phytoplankton, and total phosphorus, and we then investigated the relationships between these variables. Both data sets yielded similar long-term and short-term trends. The long-term mean annual trends were that (1) the relationships between concentrations of planktivores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 25 publications
1
8
0
1
Order By: Relevance
“…Given its proximity to these sources, the Wangjia Zhai (HP) site was expected to have higher concentrations of contaminant in the water and biota. As observed in most lake studies, we found that nutrient enrichment resulted in high algal densities at this site [McQueen et al, 1992;Carpenter et al, 1998;Smith et al, 1999]. However, the dissolved concentrations of Hg and As were lowest there and highest in the most remote site, Quan Tou.…”
Section: Discussionsupporting
confidence: 75%
“…Given its proximity to these sources, the Wangjia Zhai (HP) site was expected to have higher concentrations of contaminant in the water and biota. As observed in most lake studies, we found that nutrient enrichment resulted in high algal densities at this site [McQueen et al, 1992;Carpenter et al, 1998;Smith et al, 1999]. However, the dissolved concentrations of Hg and As were lowest there and highest in the most remote site, Quan Tou.…”
Section: Discussionsupporting
confidence: 75%
“…The availability of resources and consumption by predators have been considered key controls of the dynamics of bacterial communities. Regulation by resources and/or predators are often referred to as bottom-up and top-down control [25,26], but these concepts require some clarification when applied to bacteria. Limiting resources for bacteria are, typically, labile carbon substrates as well inorganic and organic N and P. If resource regulation is important, increases in the loading of nutrients or increases in labile carbon from, for example, phytoplankton blooms should increase bacterial biomass and productivity.…”
Section: Introductionmentioning
confidence: 99%
“…But bacteria are also significant consumers of phosphorus in pelagic systems (Rothhaupt, 1992) . Nutrient excretion, particularly P, by fish has also attracted attention recently (Braband et al, 25 1990 ;Kraft, 1992 ;McQueen et al, 1992 ;Schindler etal., 1993) .…”
Section: Introductionmentioning
confidence: 99%